Six new species of Microdon Meigen from Madagascar (Diptera: Syrphidae) - Reemer, Menno; Bot, Sander (Zootaxa, 2015)
Six new species of the myrmecophilous hoverfly genus Microdon Meigen (Diptera: Syrphidae) are described from Madagascar. Redescriptions are given for the three other Madagascan species of this genus. Keys are presented to the Madagascan genera of the subfamily Microdontinae and to the Madagascan species of Microdon.